Детская энциклопедия: [в 10 томах, в 20 книгах : перевод] (Открытие мира юношеством, 1995)
Экземпляры: аб. (1996) / Инвентарный номер: 38653 / Цена: / Сис.шифр: 63.3(0) / Авт.знак: Д 38 / ГРНТИ: 03.09 / ББК: 63.3(0)я2